DEVELOPMENT OF TISSUE CULTURE TEXTBOOK BASED ON SCIENTIFIC LITERACY AS A STUDENT LEARNING SOURCE - Fauziyah Harahap; Deliana Friska Siregar (Jurnal Pelita Pendidikan, 2021)
This study aims to develop and determine the feasibility of a tissue culture textbook based on scientific literacy, conducted from November 2020 to May 2021. This study used the Dick & Carrey development model, modified to the formative evaluation stage. The instrument used is a questionnaire filled out by validators (material experts, learning design experts, layout design experts), lecturers of the Network Culture course, and students majoring in biology. The results showed that 77% of students had difficulty learning about somaclonal diversity and needed additional cultural application material. There were no scientific literacy-based tissue culture textbooks in the UNIMED library. Based on the survey, 76.9% of students said they liked somaclonal diversity material, 86.6% said it was challenging to study, 53.8% of the material described the interaction of science, environment, technology, and society, 30.8% did not explain the application of culture. As the results of textbook development, validator analysis shows 86% (very feasible) from material experts, 91% (very feasible) from learning design experts and 91% (very feasible) from layout design experts. The percentage of responses showed: 93% (very feasible) from lecturers, 86% (very feasible) from individuals, 90% (very feasible) from small groups and 89% (very feasible) from limited groups. Overall the textbook is very feasible to use.